2021
DOI: 10.3389/fimmu.2021.652985
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-Related Disease With Tuberculosis: A Case Report and Retrospective Review of Patients in a Single Center

Abstract: BackgroundIgG4-related disease (IgG4-RD) is a recently recognized systemic fibro-inflammatory disease of unknown cause involving many organs including pancreas, salivary glands, and lymph nodes. Chronic tuberculosis (TB) infection has been reported in IgG4-RD, but the prevalence of TB infection has not been evaluated in IgG4-RD.MethodsCharacterization of a patient with IgG4-RD by physical examination, laboratory tests, magnetic resonance imaging (MRI) and histological examination. TB infection was evaluated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Only a few cases have reported the coexistence of TB and AIP as well as the potential mechanism, most of whom had type 1 AIP or IgG4-related diseases. [38][39][40] A study identified crosstalk between T-helper 17 cells and neutrophils mediated through interleukin (IL)-17A as a potential mechanism for the recruitment and subsequent destruction of neutrophils into ductal and glandular blast cells, which may be the pathognomonic for type 2 AIP. 41 TB also causes an imbalance of T-and B-lymphocytes and up to 96.7% of differentially expressed genes in TB overlap with autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few cases have reported the coexistence of TB and AIP as well as the potential mechanism, most of whom had type 1 AIP or IgG4-related diseases. [38][39][40] A study identified crosstalk between T-helper 17 cells and neutrophils mediated through interleukin (IL)-17A as a potential mechanism for the recruitment and subsequent destruction of neutrophils into ductal and glandular blast cells, which may be the pathognomonic for type 2 AIP. 41 TB also causes an imbalance of T-and B-lymphocytes and up to 96.7% of differentially expressed genes in TB overlap with autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…All TB infections in our study were detected before the diagnosis of IBD, which excluded opportunistic infections due to medical treatment. Only a few cases have reported the coexistence of TB and AIP as well as the potential mechanism, most of whom had type 1 AIP or IgG4‐related diseases 38–40 . A study identified crosstalk between T‐helper 17 cells and neutrophils mediated through interleukin (IL)‐17A as a potential mechanism for the recruitment and subsequent destruction of neutrophils into ductal and glandular blast cells, which may be the pathognomonic for type 2 AIP 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Some have suggested that IgG4-RD is precipitated by a likely unknown antigen that causes B cell differentiation into IgG4 producing plasma cells leading to the increased expression of T helper 2 (Th2) cells and cytokines [17,18]. The immune mediated response of IgG4-RD shares a similar response to tuberculosis infection as the activation of Helper T cells and the expression of similar cytokines in IgG4-RD have a crucial role in our immune mediated defense against tuberculosis infection [19,20]. As disseminated mycobacterial disease has been shown to increase a Th2 immune mediated response, it has been suggested that prolonged opportunistic infections due to underlying AOID results in activation of Th2 cells and repeated antigen exposure causes increased IgG4 production [6,21].…”
Section: Discussionmentioning
confidence: 99%
“…Serum galactomannan was detected eventually, suggestive of eventual invasive pulmonary Aspergillus, despite lack of pathological evidence of fungal invasion on biopsy. Furthermore, infections associated with IgG4-related disease have been reported with tuberculosis, 6 Necator americanus, 7 Helicobacter pylori, 8 and Paragonimus westermani. 9 It is unclear in this case if IgG4-related pulmonary disease was triggered by A subramanianii infection, or if IgG4-related disease came first, and A subramanianii infection was an infectious sequalae.…”
Section: Discussionmentioning
confidence: 99%